PENGARUH EAR, SIZE, LAR, BOPO, LDR, DAN CAR TERHADAP RETURN ON ASSET (ROA) (STUDI PADA PERUSAHAAN PERBANKAN DI BEI TAHUN 2016-2018) - Sulisnawati Sulisnawati; Salma Saleh; Nuryamin Budi; Valentinus Amstrong T. Nempung; Farhan Ramadhani Istiandar (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to determine the effect of EAR, SIZE, LAR, BOPO, LDR and CAR on Return On Assets (ROA) in banking companies listed on the Indonesia Stock Exchange. The type of research used is a type of quantitative research. The object of this study is a banking company listed on the Indonesia Stock Exchange in 2016-2018 using a purposive sampling technique, the authors chose 18 companies as samples. This study uses panel regression analysis data obtained from financial reports on the Indonesia Stock Exchange (IDX) website. The research period is 3 years. This study uses secondary data with the help of the Eviews application. The results of the study found that EAR had a negative and significant effect on ROA, SIZE had a positive and significant effect on ROA, LAR had a negative and insignificant effect on ROA, BOPO had a positive and significant effect on ROA, LDR had a positive and insignificant effect on ROA, and CAR had a negative and significant effect on ROA. significant not significant to ROA.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//